Effect of rifampicin and efavirenz on moxifloxacin concentrations when co-administered in patients with drug-susceptible TB - Naidoo, Anushka (J Antimicrob Chemother, 2017)
Objectives: We compared the pharmacokinetics of moxifloxacin during rifampicin co-treatment or when dosed alone in African patients with drug-susceptible recurrent TB. Methods: Patients in the intervention arm of the Improving Retreatment Success (IMPRESS) randomized controlled TB trial received 400 mg of moxifloxacin, with rifampicin, isoniazid and pyrazinamide in the treatment regimen. Moxifloxacin concentrations were measured in plasma during rifampicin-based TB treatment and again 4 weeks after treatment completion, when given alone as a single dose. Moxifloxacin concentration–time data were analysed using non-linear mixed-effects models. Results: We included 58 patients; 42 (72.4%) were HIV co-infected and 40 (95%) of these were on efavirenz-based ART. Moxifloxacin pharmacokinetics was best described using a two-compartment disposition model with first-order lagged absorption and elimination using a semi-mechanistic model describing hepatic extraction. Oral clearance (CL/F) of moxifloxacin during rifampicin-based TB treatment was 24.3 L/h for a typical patient (fat-free mass of 47 kg), resulting in an AUC of 16.5 mg·h/L. This exposure was 7.8% lower than the AUC following the single dose of moxifloxacin given alone after TB treatment completion. In HIV-co-infected patients taking efavirenz-based ART, CL/F of moxifloxacin was increased by 42.4%, resulting in a further 30% reduction in moxifloxacin AUC. Conclusions: Moxifloxacin clearance was high and plasma concentrations low in our patients overall. Moxifloxacin AUC was further decreased by co-administration of efavirenz-based ART and, to a lesser extent, rifampicin. The clinical relevance of the low moxifloxacin concentrations for TB treatment outcomes and the need for moxifloxacin dose adjustment in the presence of rifampicin and efavirenz co-treatment need further investigation.